Tropine exacerbates the ventilatory depressant actions of fentanyl in freely-moving rats - Getsy, Paulina M.; May, Walter J.; Young, Alex P.; Baby, Santhosh M.; Coffee, Gregory A.; Bates, James N.; Hsieh, Yee-Hsee; Lewis, Stephen J. (Frontiers in Pharmacology, 2024)
Our lab is investigating the efficacy profiles of tropine analogs against opioid-induced respiratory depression. The companion manuscript reports that the cell-permeant tropeine, tropine ester (Ibutropin), produces a rapid and sustained reversal of the deleterious actions of fentanyl on breathing, alveolar-arterial (A-a) gradient (i.e., index of alveolar gas exchange), and arterial blood-gas (ABG) chemistry in freely-moving male Sprague Dawley rats, while not compromising fentanyl analgesia. We report here that in contrast to Ibutropin, the injection of the parent molecule, tropine (200 μmol/kg, IV), worsens the adverse actions of fentanyl (75 μg/kg, IV) on ventilatory parameters (e.g., frequency of breathing, tidal volume, minute ventilation, peak inspiratory and expiratory flows, and inspiratory and expiratory drives), A-a gradient, ABG chemistry (e.g., pH, pCO2, pO2, and sO2), and sedation (i.e., the righting reflex), while not affecting fentanyl antinociception (i.e., the tail-flick latency) in freely-moving male Sprague Dawley rats. These data suggest that tropine augments opioid receptor-induced signaling events that mediate the actions of fentanyl on breathing and alveolar gas exchange. The opposite effects of Ibutropin and tropine may result from the ability of Ibutropin to readily enter peripheral and central cells. Of direct relevance is that tropine, resulting from the hydrolysis of Ibutropin, would combat the Ibutropin-induced reversal of the adverse effects of fentanyl. Because numerous drug classes, such as cocaine, atropine, and neuromuscular blocking drugs contain a tropine moiety, it is possible that their hydrolysis to tropine has unexpected/unintended consequences. Indeed, others have found that tropine exerts the same behavioral profile as cocaine upon central administration. Together, these data add valuable information about the pharmacological properties of tropine.